Fitri Tomyam Seafood Menu Order Android Mobile Application - Mohamad Zaki, Mazuda; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2021)
Fitri Tomyam Seafood Menu Order Android Mobile Application is an android based mobile application that was developed to aid the business process in the aspect of delivery orders for Fitri Tomyam Seafood restaurant. The existing manual process of taking delivery orders where delivery orders are taken via WhatsApp platform is not an efficient method in managing delivery orders and provides poor customer service. Therefore, to build this project, an object oriented software development method was used in this project. Whereas, this application was developed using Android Studio and Firebase database. Overall, Fitri Tomyam Seafood Menu Order Android Mobile Application enables this restaurant to provide better customer service in delivery orders.